(untitled) (Asian Journal of Ethnobiology, 2025)
Abstract. Afrianto WF. 2025. Ethnobotanical documentation of home gardens in relation to Javanese basic life needs in Kediri District, East Java, Indonesia. Asian J Ethnobiol 8: 79-91. Home gardens, as traditional agroforestry approaches, not only promote plant diversity but also support human livelihoods. The Javanese community exhibits distinct cultural practices in the utilization of plant species in home gardens. This study examines the plant species utilized by the Javanese based on five dimensions of basic life needs. Data were collected from 55 home gardens through purposive sampling and analyzed based on Javanese philosophy: nourishment (pangan), clothing (sandang), shelter (papan), herbal medicine (loro), and traditional death-related rituals (pati). Information on all plants and their uses was directly obtained from respondents. The ethnobotany R package assessed the ethnobotanical importance of these plants. A total of 71 plant species from 43 families were identified, with trees being the most common life form and fruit-bearing plants dominating the community. The plants were mainly used as food (53 species), followed by medicine (17 species), construction (9 species), ritual (6 species), and clothing (1 species). Notably, Moringa oleifera Lam. and Bambusa sp. were found to serve three use categories. Ethnobotanical indices showed that Mangifera indica L. had the highest values. The study highlights that plant conservation in Javanese home gardens can be effectively achieved through cultural approaches. The role of sustainable home gardens in managing household and community food security and nutritional needs is significant and promising.